Effects of Climate Change on Northern Bobwhite Nesting Chronology and Clutch Size - Justin A Rectenwald; D. Clay Sisson; James A. Martin (National Quail Symposium Proceedings, 2022)
Widespread changes to breeding bird phenology in response to climate change have been apparent in North America for several decades. While the impact of an earlier breeding season may be minimal by itself, changes in community-level interactions can be greatly influenced because of varying responses to climate change in different trophic levels. Climate change has been shown to alter the onset of breeding season and chick survival, and lead to population declines for game birds in high latitudes, at high elevations, and on the periphery of their range. The topic of climate change in relation to northern bobwhite (Colinus virginianus; hereafter, bobwhite) populations has attracted interest in the past 2 decades. Some researchers have hypothesized that climate change has the potential to cause the breeding season to initiate sooner and have a shorter duration. Using a 29-year dataset (1992–2020) with 1,171 individual bobwhites, we analyzed how temperatures prior to the breeding season affected the timing of nest initiation and clutch size, and how the length of the breeding season varied over time. We determined that the average minimum daily temperatures 30 days prior to the breeding season warmed by 0.07° C/year from 1992–2020. For any given year, we found that nest initiation could occur 1.12 days earlier for every 1° C increase in temperature. Overall, we determined that the timing of the nesting season had not changed from 1992–2020. The overall average breeding season length (135 days) or last average initiation date (27 Aug) did not change over the course of our study. We did not find that clutch sizes have changed over time and they were not correlated to pre-laying temperature. We attribute the lack of significant change in nesting chronology to plasticity of populations within the core of the range and the intensity of bobwhite management on the landscape.
Keywords: breeding phenology; Colinus virginianus; nest initiation; temperature